(untitled) (Revista Universidad Católica de Oriente, 2024)
Twenty-nine emulsions were proved experimentally to implement them as a form of treatment for Water Retention efficiency (WR) and prevention of rapid evaporation of free water on concrete. All emulsions were evaluated in two different concentrations of Total Dissolve Solids (TDS) (at lower level 10 %-15 % w/w and at higher level 27 %-30 % w/w). At higher TDS, cationic emulsion B2 showed the best percentage of WR 91 % (IC 95 %97.5% - 99.99%). There were others emulsions that present a significant response of WR (emulsions G non-ionic, F non-ionic and G2 cationic). At lower level of TDS, emulsion D has showed to be the best with 74 % of WR, therefore emulsions A1, A3, B, C, E had very good water retention with 95 % CI ranged from 52 % to 74 %. All emulsions evaluated at lower TDS showed worst WR than emulsion evaluated at higher TDS (B2, G, F and G2). In a multivariate analysis, environmental variables like relative moisture (RLV), Temperature and Water Adding (Water.gr) have not affected. However, interaction of high levels of RLV and lower levels of temperature showed a positive correlation with retention water in emulsions G2 and D after 72 hours of drying. In conclusions cationic emulsions G, F, G2 and B2 evaluated at higher level of TDS were better than those evaluated at lower level of TDS. To implement curing compound for concrete is not recommended to use curing compounds at lower levels of TDS.